The Effect of Perceived Risk and Perceived Benefit on Online Shopping Behavior with Trust as Moderator and Attitude as Mediator - Kurniawan, Shelvy; Agustine, Aulivia Dewi; Kamada, Erika; Suprapto, Laudhinar Nurtriara Kamal (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
The rapid development of technology in the field of e-commerce has brought forth numerous ways for consumers to make purchases online. The phenomenon of online shopping conducted by society is inseparable from the risks and benefits that people experience when engaging in online shopping. This research aims to analyze the influence of perceived risk which includes product risk, privacy risk, and convenience risk moderated by trust on online shopping behavior, and the influence of perceived benefit mediated by attitude on online shopping behavior. The research scope of this study is limited to the generation Z which shops on the online fashion industry. The research employs a quantitative research methodology, and data collection is done through questionnaire with 383 respondents who met the research criteria, namely Indonesian generation Z who had purchased fashion products on e-commerce platforms. The results of data analysis indicate that product risk, privacy risk, convenience risk, and perceived benefit significantly influence the online shopping behavior variable. Trust as a moderating variable has a significant effect on the product risk, privacy risk, and convenience risk variables. Attitude as a mediating variable between perceived benefit and online shopping behavior also has a significant influence on online shopping behavior.